Novel Bis-Thiazole Derivatives: Synthesis and Potential Cytotoxic Activity Through Apoptosis With Molecular Docking Approaches - Dawood, Kamal M.; Raslan, Mohamed A.; Abbas, Ashraf A.; Mohamed, Belal E.; Abdellattif, Magda H.; Nafie, Mohamed S.; Hassan, Mohamed K. (Frontiers in Chemistry, 2021)
A series of bis-thiazoles 5a-g were synthesized from the bis-thiosemicarbazone 3 with hydrazo-noyl chlorides 4a-g. Reaction of 3 with two equivalents of -halocarbonyl compounds 6-8, 10 and 12a-d afforded the corresponding bis-thiazolidine 9, 11 and 13a-d, respectively. Condensation of bis-thiazolidin-4-one 9 with different aromatic aldehydes furnished the bis-thiazolidin-4-ones 14a-d. Compounds 5a-g, 9 and 13a,c,d were screened in vitro for their cytotoxic activities in a panel of cancer cell lines. Compounds 5a-c, 5f-g, and 9 exhibited remarkable cytotoxic activities, especially compound 5c with potent IC50 value 0.6 nM (against cervical cancer, Hela cell line) and compound 5f with high IC50 value 6 nM (against ovarian cancer, KF-28 cell line). Compound 5f induced appreciated apoptotic cell death measured 82.76% associated with cell cycle arrests at the G1 phase. The apoptotic pathway(s) activated in KF-28 cells treated by 5a, 5b and 5f were fur-ther investigated. The upregulation of some pro-apoptotic genes, bax and puma, and the down-regulation of some anti-apoptotic genes including bcl2 gene were observed, indicating activation of the mitochondrial-dependent apoptosis. Together with the molecular docking studies of com-pounds 5a and 5b, our data revealed potential Pim-1 kinase inhibition through their high binding affinities which indicated by inhibition of phosphorylated C-myc as a downstream target for Pim-1 kinase. Our study introduces a set of bis-thiazoles with potent anti-cancer activities, in vitro.